SANGER CUSTOMARY LAW IN THE MUSLIM COMMUNITY OF DANA SEMBULUH VILLAGE, DANA SEMBULUH DISTRICT, SERUYAN REGENCY - Yusril Anwar Ibrahim; Abdul Khair; Novita Mayasari Angelia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The purpose of this study is to identify and analyze the implementation of physical sanctions in Sanger customary law, which is practiced within the Muslim community of Danau Sembuluh Village, Danau Sembuluh District, Seruyan Regency, as well as the Islamic legal perspective on these physical sanctions in Sanger customary law within the same community. A qualitative research method was employed, using a field research approach, with the findings presented descriptively (in the form of words or sentences). Regarding the research approach, the study adopts a socio-legal perspective, meaning that it focuses on legal aspects as perceived by the community, particularly concerning the application of physical sanctions in Sanger customary law, which is then examined through the lens of Islamic law. The findings indicate that the implementation of physical sanctions in Sanger customary law in Danau Sembuluh Village, Danau Sembuluh District, Seruyan Regency—including within its Muslim community—adheres to principles aligned with the legal framework of Indonesia, namely kinship, justice, and deliberation in the interest of the collective good. From an Islamic legal perspective, this practice falls under the category of al-'Urf al-Shahih (valid customary practice), as it promotes maslahah (benefit) and prevents mufsadah (harm). However, if the application of such sanctions involved oppression, disproportionality, or exceeded reasonable limits, it would instead be classified as al-'Urf al-Fasid (corrupt customary practice), which is deemed invalid. This distinction aligns with the principles outlined in the Qur'an, Hadith, and the opinions of Islamic scholars.